Peran dan Tanggung Jawab Pejabat Pembuat Akta Tanah Dalam Penyelenggaraan Sistem Pendaftaran Tanah - Purnamawati, Ni Luh Gede; Kurniawan, I Gede Agus (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
The aim of this research is to better understand the duties and responsibilities of land deed officials in the implementation of the land registration system. Land registration with Land Deed Officials is proven to still cause various legal problems. This writing uses normative research methods to investigate the roles and responsibilities of land deed officials in the land registration system, using statutory approaches, conceptual approaches, and primary, secondary, and tertiary legal materials. The results of the study show that the Land Deed Making Officer in the implementation of land registration is very important to ensure the legality and legitimacy of the transfer of land rights and to maintain legal certainty for all parties involved in land transactions. Where the PPAT's responsibility is very important in ensuring that all land rights transfer transactions are carried out lawfully, legally, and in accordance with applicable legal provisions. Thus the purpose of land registration can be achieved.